X=(5-2i)(1+3i)

Simple and best practice solution for X=(5-2i)(1+3i) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X=(5-2i)(1+3i) equation:



X=(5-2X)(1+3X)
We move all terms to the left:
X-((5-2X)(1+3X))=0
We add all the numbers together, and all the variables
X-((-2X+5)(3X+1))=0
We multiply parentheses ..
-((-6X^2-2X+15X+5))+X=0
We calculate terms in parentheses: -((-6X^2-2X+15X+5)), so:
(-6X^2-2X+15X+5)
We get rid of parentheses
-6X^2-2X+15X+5
We add all the numbers together, and all the variables
-6X^2+13X+5
Back to the equation:
-(-6X^2+13X+5)
We get rid of parentheses
6X^2-13X+X-5=0
We add all the numbers together, and all the variables
6X^2-12X-5=0
a = 6; b = -12; c = -5;
Δ = b2-4ac
Δ = -122-4·6·(-5)
Δ = 264
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{264}=\sqrt{4*66}=\sqrt{4}*\sqrt{66}=2\sqrt{66}$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-12)-2\sqrt{66}}{2*6}=\frac{12-2\sqrt{66}}{12} $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-12)+2\sqrt{66}}{2*6}=\frac{12+2\sqrt{66}}{12} $

See similar equations:

| 7p+2(p+6)=39 | | (2/b)=20 | | 9+7n=-75 | | 1+4m=3m+5 | | 8x+2(X-1)=5x+5(x-3) | | 4x=8x^-1 | | 11(x+5)+3=-30 | | 6(6x+6)+8(6x+5)=123 | | 5=v/10+4 | | 54+2x+(x-2)=180 | | (5x+27)+(8x)=180 | | 2.3^x-1-8=10 | | (1÷2)+4m=3m+(5÷2) | | 18a-17=-161 | | x7-4=5 | | 47.7=9.6h+18.9 | | 4x-4=2(3x+1)-4x | | 2+5n=(n+2)-7 | | -0.71x+0.51x=4.6 | | 6x+2=13x-61 | | –8s=–9s−3 | | Y=5n2 | | (4x+24)=20 | | (20p/4)=5 | | 2(d+18)=-3(d+18) | | -7n-5=-110 | | 2(x+1)=x+x+2 | | 4x+13=2x+25 | | 1/2(4x+24)=20 | | Y=-5n | | 130=130-6t-16t^2 | | 11=v/5-10 |

Equations solver categories